A novel classification of tracheal defects and the reconstruction strategies: A retrospective study based on 106 cases. Issue 1 (29th April 2022) - Xia, Xin; Zhu, Xiao‐Li; Zhu, Ying‐Ying; Diao, Wen‐Wen; Chen, Xing‐Ming
Abstract: Objective: The study aims to present a novel classification of tracheal defects and the corresponding reconstruction strategies. Methods: The retrospective study was designed to analyze patients with diagnosed primary or secondary tracheal tumors from 1991 to 2020. Surgical techniques, complications and prognosis were reviewed. Airway status and patient outcomes were the principal follow‐up measures. Tracheal defects were classified into two plane sizes (vertical (V) and horizontal (H) planes). Vertical defects were further categorized into three groups based on their tracheal ring numbers (V1, ≤ 5 rings; V2, 6‐10 rings; and V3, > 10 rings). Tracheal defects with horizontal plane size H1 and H2 represent defects less and more than one‐half the circumference of trachea. Thus, suitable reconstruction strategies were planned primarily based on "V" and "H" classifications. The reconstruction strategies performed were sleeve resection followed by an end‐to‐end anastomosis, window resection with sternocleidomastoid myoperiosteal flap reconstruction, defects conversion with rotation anastomosis, and modified tracheostomy with secondary flap reconstruction. Results: A total of 106 patients diagnosed with tracheal defects were enrolled in the study, of whom 59 patients underwent sleeve resection followed by end‐to‐end anastomosis; 40 patients received window resection alongside sternocleidomastoid (SCM) myoperiosteal flap reconstruction; five patients received converting defects with rotation anastomosis and two patients underwent modified tracheostomy with secondary stage flap reconstruction. Lumen stenosis occurred in three V2 H1 defect cases and were treated by a second reconstruction surgery. Iatrogenic unilateral recurrent laryngeal nerve paralysis occurred in two patients with the V3 H2 defect type, who were treated by temporary tracheotomy and partial vocal cord resection and extubated successfully during follow‐up. All 106 patients achieved airway patency with adequate laryngeal function at the end of follow‐up. No anastomotic dehiscence or bleeding occurred in any patient postoperatively. Conclusion: Though a significant number of multicenter studies concerning the reconstruction and classification of tracheal defects are needed, the study herein provides a novel classification of tracheal defects, which is primarily developed on the defect size. Therefore, the study might serve as a potential source for identifying suitable reconstruction strategies for practitioners.